A Review of Sensors for the Monitoring, Modeling, and Control of Commercial Wine Fermentations - Roger Boulton; James Nelson; André Knoesen (Fermentation)
Large-scale commercial wine fermentation requires the monitoring and control of multiple variables to achieve optimal results. Challenges in measurement arise from turbidity, stratification in large unmixed volumes, the presence of grape skins and solids during red wine fermentations, the small changes in variables that necessitate precise sensors, and the unique composition of each juice, which makes every fermentation distinct. These complications contribute to nonlinear and time-variant characteristics for most control variables. This paper reviews sensors, particularly online ones, utilized in commercial winemaking. It examines the measurement of solution properties (density, weight, volume, osmotic pressure, dielectric constant, and refractive index), sugar consumption, ethanol and glycerol production, redox potential, cell mass, and cell viability during wine fermentation and their relevance as variables that could enhance the estimation of parameters in diagnostic and predictive wine fermentation models. Various methods are compared based on sensitivity, availability of sensor systems, and their appropriateness for measuring properties in large commercial wine fermentations. Additionally, factors influencing the adoption of control strategies are discussed. Finally, potential opportunities for control strategies and challenges for future sensor developments are outlined.